Diseño de un modelo de intervención en convivencia a partir de los indicadores de clima escolar en la institución educativa distrital “San Gabriel” de Barranquilla (2015)
The purpose of the present research is to design a model of intervention in the school community designed to prevent and reduce conflict manifestations in I.E.D San Gabriel, a public school in Barranquilla, from indicators of school atmosphere. The sample was 280 students, which is equivalent to 56.11% of the student community from sixth to eleventh grades of this institution, between 10 and 15 years. The socio economic status of students goes from medium to low level. This research used a method of quantitative descriptive approach, it sought to determine, through objective data collection, students' perception on school climate and school conflict through a quantitative phase to allow through analysis and interpretation of intervention build a model of coexistence. Through this research, the perceptions of school atmosphere and school demonstrations conflict between student pairs of the institution were determined. Therefore, the proposed design of a model of intervention in school community.